2008
DOI: 10.1007/s10350-008-9349-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rectal Sensory and Motor Function by Means of the Electronic Barostat After Stapled Hemorrhoidopexy

Abstract: Rectal distensibility and volume thresholds for sensations decrease after stapled hemorrhoidopexy. These impairments persist for at least six months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…Both proctalgia and urgency, for instance, may be due to a reduction in the rectal reservoir after PPH, as shown by De Nardi et al using a barostat [11]. Soiling may be due to the deficient sphincters stretched by the transanally introduced stapling technique, as shown by Ho et al [12] who found internal anal sphincter fragmentation on anal ultrasonography.…”
Section: Discussionmentioning
confidence: 93%
“…Both proctalgia and urgency, for instance, may be due to a reduction in the rectal reservoir after PPH, as shown by De Nardi et al using a barostat [11]. Soiling may be due to the deficient sphincters stretched by the transanally introduced stapling technique, as shown by Ho et al [12] who found internal anal sphincter fragmentation on anal ultrasonography.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the cross-check of the publications provided data from additional seven publications dealing with agraffectomy for sequelae after stapling procedures [8,9,[18][19][20][21][22]. In the present review, the potential effect of agraffectomy is evaluated with respect to the complicating conditions after SHP.…”
Section: Resultsmentioning
confidence: 99%
“…One cause of fecal urgency/incontinence after SHP may be muscle contraction in response to nerve and/or muscle irritation which would cause decreased rectal compliance [18]. Kam et al [28] showed that some smooth muscle is invariably excised in SHP but the amount of smooth muscle removed did not significantly affect the continence score, quality of life, or mean anal resting pressure after SHP.…”
Section: Fecal Urgency and Incontinencementioning
confidence: 99%
“…Zusätzlich lieferte die Prüfung der Literaturverzeichnisse Daten von weiteren 7 Publikationen, die sich mit Agraffektomie wegen Folgekomplikationen nach Staplereingriffen [8,9,[18][19][20][21][22] befassten. Im vorliegenden Review wird die potenzielle Auswirkung der Agraffektomie nach Komplikationen einer SHP evaluiert.…”
Section: Ergebnisseunclassified
“…Ein Grund für Stuhldrang/Inkontinenz nach SHP kann eine Muskelkontraktion als Antwort auf Nerven-und/oder Muskelirritation sein, die eine geminderte rektale Compliance verursacht [18]. Kam et al [28] zeigten, dass bei der SHP immer auch ein wenig glatte Muskulatur entfernt wird.…”
Section: Introductionunclassified